Identification of a novel FGFR2-KIAA1217 fusion in esophageal gastrointestinal stromal tumours: A case report - Luo, Yuehao; Wu, Ying; Chang, Xiaona; Huang, Bo; Luo, Danju; Zhang, Jiwei; Zhang, Peng; Shi, Heshui; Fan, Jun; Nie, Xiu (Frontiers in Oncology, 2022)
Background: Gastrointestinal stromal tumours (GISTs) rarely arise in the oesophagus. The clinical course and treatment options for oesophageal GISTs are poorly understood because of their rarity. In general, the mutation spectrum of oesophageal GISTs resembles that of gastric GISTs. Wild-type (WT) GISTs lacking KIT and PDGFRA gene mutations occasionally occur in adults; primary oesophageal GISTs are commonly WT. Case presentation: Herein, we report the case of a 41-year-old female patient who presented with a 1-week history of anterior upper chest pain. Chest computed tomography revealed a 3.7 cm × 2.8 cm × 6.7 cm soft tissue mass in the right posterior mediastinum adjacent to the oesophagus. The patient underwent thoracoscopic mediastinal tumour resection and was subsequently diagnosed with an oesophageal GIST. Neither KIT nor PDGFRA mutations were detected by Sanger sequencing; however, next-generation sequencing (NGS) identified an FGFR2-KIAA1217 gene fusion in the tumour tissue. No relapse was observed in this patient during the 8-month treatment-free follow-up period. Conclusion: To the best of our knowledge, this report is the first to describe an FGFR2-KIAA1217 fusion in a patient with a quadruple WT oesophageal GIST. When WT KIT/PDGFRA GISTS are suspected, intensive genetic analysis is recommended, and obtaining a better molecular characterization of these tumours might reveal novel therapeutic avenues.